New global standard set for metro networks.
The International Telecommunication Union (ITU) has removed a barrier to better short-haul optical communication networks in urban centers with the approval of a new standard. Officially known as ITU-T Recommendation G.694.2, the new standard specifies a set of wavelengths for use in what are known as coarse wavelength-division multiplexing (CWDM) systems. Unlike dense wavelength-division multiplexing (DWDM), in which wavelengths are spaced less than a nanometer apart, the new standard for CWDM specifies 20-nm spacing.
Keywords: 20 nm; CWDM systems; ITU; ITU-T Recommendation G.694.2.; International Telecommunication Union; Coarse wavelength-division multiplexing; Short-haul optical communication networks; Urban centers; Wavelengths